The pristine Dao : metaphysics in early Daoist discourse - Michael, Thomas, 1966- (SUNY series in Chinese philosophy and culture., 2005)
"The Laozi (Daodejing) and the Zhuangzi have long been familiar to Western readers and have served as basic sources of knowledge about early Chinese Daoism. Modern translations and studies of these works have encouraged a perception of Daoism as a mystical philosophy heavy with political implications that advises kings to become one with the Dao. Breaking with this standard approach, The Pristine Dao argues that the Laozi and the Zhuangzi participated in a much wider tradition of metaphysical discourse that included a larger corpus of early Chinese writings."--Jacket